Analisis adaptive reasoning proficiency mahasiswa melalui implementasi teori conditioning-reinforcement-scaffolding (CRS) pada mata kuliah analisis real - Karunia Eka Lestari; Mokhammad Ridwan Yudhanegara (JP3M (Jurnal Penelitian Pendidikan dan Pengajaran Matematika), 2017)
The research approach used in this research is the quantitative approach. The quantitative study is done through experimental research method by giving treatment through CRS theory implementation in Real Analysis lecture. Provision of treatment directed to improve student’s adaptive reasoning proficiency. The research design used was quasi-experimental with the design form of matching-only pretest-posttest control group design. Population in this research is all student of semester IV of academic year 2016/2017 Program of the Mathematics Education University of Singaperbangsa Karawang who contract Real Course of Analysis, and a sample of this research involves two groups of students selected using purposive sampling technique with matching the subject. Matching the subject is done by pairing individuals based on certain criteria. These criteria are determined based on placement test results before pretesting. This is done in an effort to obtain an equivalent group. The result of the research concludes that 1) The improvement of the adaptive reasoning proficiency of students who get the learning through the implementation of CRS theory does not reach 70% of ideal criteria expected. 2) Increased adaptive reasoning proficiency of students who get learning through the implementation of CRS theory is higher than students who get learning through the implementation of constructivism theory. 3) There is an adaptive difference in reasoning proficiency of students who get learning through the implementation of CRS theory based on achievement of adaptive indicators of reasoning proficiency. 4) There is no interaction between learning factor with achievement factor of adaptive reasoning proficiency toward student’s adaptive reasoning proficiency in real analysis course.